Enhanced Soil Chemical Properties and Rice Yield in Acid Sulphate Soil by Application of Rice Straw - Siti Nurzakiah; Linda Indrayati; . Nurita (JOURNAL OF TROPICAL SOILS, 2012)
Swampland development such as acid sulphate soil for agricultural cultivation has various problem, including high soil acidity, fluctuated and unpredictable water flooding and the presence of toxic elements such as Fe which resulting in low crop yields. The research was conducted at the experimental station Belandean, Barito Kuala regency in dry season 2007.  The objective of research was to study the effect of rice straw on the dynamic of soil pH, the concentration of iron and sulphate and yield on tidal land acid sulphate soil at two different water inlet channel. This research was designed in RCBD (Randomized Completely Block Design) with five treatments (0, 2.5, 5.0, 7.5 and 10 Mg ha-1) and four replications. Dolomite as much as 1 Mg ha-1 was also applied.  This research was divided into two sub-units experiment i.e. two conditions of different water inlet channel. The first water channels were placed with limestone and the second inlet was planted with Eleocharis dulcis.  The results showed that (i) rice straw application did not affect the dynamic of soil pH, concentration of iron and sulphate, and (ii) the highest yield was obtained with 7.5 Mg ha-1 of rice straw.